Green Accounting in Healthcare: Strategic Framework for Sustainable Hospital Management - Kadek Nita Sumiari; I Gusti Ayu Astri Pramitari; I Made Adhi Wirayana; I Ketut Parnata; Ni Luh Putri Setyastrini (Institut Bisnis dan Informatika Kesatuan, 2025)
The healthcare sector plays a vital role in improving human well-being, but also significantly contributes to environmental degradation through high energy consumption, resource use, and waste generation. In response to these environmental challenges, green accounting emerges as a strategic tool to integrate environmental costs into financial decision-making and promote sustainable hospital operations. This study examines the key components, implementation strategies, and real-world applications of green accounting in the healthcare industry, with a focus on environmental cost accounting, performance indicators, and green financial reporting. Using the qualitative method, drawing on global case studies including hospitals in the United States, the United Kingdom, Singapore, India, and South Africa, the research identifies effective practices and outcomes such as carbon footprint reduction, operational cost savings, and enhanced stakeholder engagement. While challenges persist, such as a lack of standardized metrics, limited technical infrastructure, and financial constraints, green accounting proves to be a transformative approach that aligns ecological responsibility with healthcare excellence. The study recommends policy support, digital infrastructure development, and staff engagement as critical enablers for mainstreaming sustainability in hospital management.